2022
DOI: 10.3389/fcimb.2022.914247
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Gut Microbiota and Fecal Bile Acid Profiles in Children With Biliary Atresia

Abstract: BackgroundBiliary atresia (BA) is the most common cholestatic liver disease in neonates. Herein, we aimed at characterizing the gut microbiota and fecal bile acid profiles of BA patients, defining the correlations between them, and evaluating the relationship between the clinical pathogenesis and changes in the gut microbiota and bile acid profiles.MethodsA total of 84 fecal samples from BA patients (n = 46) and matched healthy controls (HCs, n = 38) were subjected to sequencing by 16S rRNA gene amplification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Recently, the role of intestinal flora in BA has received attention. A disturbed gut microbiota structure was identified in the BA group [ 52 ] and correlated with the occurrence of postoperative cholangitis and jaundice clearance [ 53 , 54 ]. Wang et al conducted 16S ribosomal RNA gene sequencing on the intestinal flora of 16 BA patients after surgery in 2020, and the results showed that the intestinal flora diversity of BA patients decreased and the overall structure changed, among which the proportion of Clostridium decreased significantly [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of intestinal flora in BA has received attention. A disturbed gut microbiota structure was identified in the BA group [ 52 ] and correlated with the occurrence of postoperative cholangitis and jaundice clearance [ 53 , 54 ]. Wang et al conducted 16S ribosomal RNA gene sequencing on the intestinal flora of 16 BA patients after surgery in 2020, and the results showed that the intestinal flora diversity of BA patients decreased and the overall structure changed, among which the proportion of Clostridium decreased significantly [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colidextribacter was significantly positively correlated with pro-inflammatory factors, negatively correlated with antioxidant enzyme activities and anti-inflammatory factors [ 51 ], and significantly reduced the abundance of Colidextribacter in the colon in weaned piglet diets supplemented with probiotics Clostridium butyricum [ 18 ]. In addition, there are few reports on norank_f__Selenomonadaceae , which belongs to the family level Selenomonadaceae and is enriched in patients with episodes of cholangitis [ 52 ]. Correlation analysis also showed that norank_f__Selenomonadaceae and Colidextribacter were significantly negatively correlated with serum immune indexes (IgG, IgM), antioxidant index T-AOC, and intestinal-barrier-related indexes (ZO-1, Occludin).…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Blautia is a new functional genus with putative probiotic properties. [ 49 ] Moreover, as the dominant genus of bacteria in kefir‐treated mice, Parasutterella has impacted BA transport and synthesis and thereby participated in the maintenance of BA homeostasis. [ 50 ] In conclusion, bacterial alterations in alcohol‐related diseases are largely characterized by reductions in beneficial communities and increases in the pathogenic taxa.…”
Section: Discussionmentioning
confidence: 99%